Informe dictamen: [vinculación de dirigentes del MIR con el narcotráfico] - Granado Cosio, Juan del (Comision de Constitución, Justicia y Policía Judicial, 1994)
"Remarkable document presents findings of a congressional commission that investigated charges against former president Jaime Paz Zamora and the leadership of his party, the Movimiento de Izquierda Revolucionaria (MIR). Commission concluded that the evidence warranted an indictment of Zamora and three other MIR leaders. As a result of this report, Oscar Eid Franco, one of the MIR's principal leaders, was tried and sentenced to a four-year jail term"--Handbook of Latin American Studies, v. 57